Morphological and Anatomical Variations among Alocasia alba Schott Accessions in Bali Botanic Garden - Ni Putu Sri Asih; Ema Hendriyani; Eka Fatmawati Tihurua (Universitas Gadjah Mada, 2022)
Alocasia alba Schott is a member of Macrorrhizos group from Aroid family that has conserved in Bali Botanic Garden. On its development, the collections showed varied morphological diversity on leaves and flowers. The aim of this study is to fill the knowledge gap in morphology and anatomy of the species A. alba and to know the phenotypic variation in this species. A total of eight A. alba accessions from Java, Bali and West Nusa Tenggara were observed in morphological and anatomical characters. The result showed that the eight accessions of A. alba have some variations in morphological and anatomical characters. These variations might be caused by genetic factors that resulted from plant adaptation to the different environments.